Australian Union Transformation and the Challenge for Labour Historians. (May 2020) - Bowden, Bradley
Abstract : The purpose of this article is two-fold. First, it confronts misconceptions that explain union decline in Australia; misconceptions that are entrenched in labour history and industrial relations scholarship. We are told that decline "commenced in the early 1980s, " when in fact it began in 1948; that union decline primarily results from attacks by conservative governments "bent on their destruction, " when the rate of decline has often been steepest under Labor governments; that unions invariably redress the plight of society's poorest, when union agreements negotiated in retail and hospitality routinely leave workers in a worse position than those employed under relevant awards. The article's second purpose is to trace the sociological consequence of union decline. While unions claim to speak for society's battlers, more than 40 per cent of unionists today are managers and professionals. In terms of wage cohorts, the propensity to join increases with wealth. Although unions retain representation rights for society's battlers, and publicly advocate their cause, the fact remains: society's poorest members are no longer found in much number in union ranks. In part, at least, the unwillingness of labour historians to confront harsh realities stems from an understandable desire to defend labour's cause, rather than serve primarily as dispassionate academic observers.